Turunkan Populasi Nyamuk Penular Demam Berdarah Dengue (DBD) Di Wilayah Sporadik Dengan Pemantauan Jentik Berkala - Abdul hamid; Iga Maliga; Ana Lestari (CV. Multi Kreasi Media, 2023)
Dengue Hemorrhagic Fever (DHF) is still a major public health problem in Indonesia. The number of sufferers and the area of ​​distribution is increasing along with increasing mobility and population density. Environmental-based diseases are still a public health problem until now. This community service aims to increase community participation in eradicating dengue fever mosquito nests with DHF PSN (3M Plus) through a Larvae Monitor (Jumantik). The target of this community service activity is the community members in the Berare Village Environment, Kec. Sumbawa Regency Sumbawa, The benefits of this community service activity are as a step for us to reduce the population of mosquitoes that transmit dengue fever (DHF) Aedes Aegypty and their larvae by increasing community participation in eradicating mosquito breeding grounds for dengue fever with PSN (3 M plus) through larva monitors . This activity was carried out on Saturday 26 November 2022 with social action to reduce the population of mosquitoes that transmit dengue fever (DHF) in sporadic areas with periodic larva monitoring involving the community and students of the STIKES Griya Husada Sumbawa Public Health Study Program. Jumantik is a form of movement or active participation from the community in tackling DHF (Dengue Hemorrhagic Fever). For this reason, through periodic monitoring of mosquito larvae, it is hoped that the number of cases of DHF transmission will decrease and it is hoped that jumantik rumah cadres can check their own larvae every week and can increase public awareness to always maintain cleanliness in order to prevent the development of dengue